Gendering classicism : the ancient world in twentieth-century women's historical fiction - Hoberman, Ruth (State University of New York Press, 1997)
Gendering Classicism explores the intersection of feminism, historical fiction, and modernism through the work of six writers, all of whom wrote historical novels set in ancient Greece or Rome: Naomi Mitchison, Mary Butts, Laura Riding, Phyllis Bentley, Bryher, and Mary Renault. As women gained access to higher education in the late nineteenth century, they gained access also to the classical learning that had for so long demarcated and legitimated the British ruling classes. Steeped in misogyny, the classical tradition presented educated women with a massive project: the recasting of that tradition in terms that acknowledged the existence of women - as historical agents and interpreters of the historical past.